Web Development Using ReactJS - Keshari, Pankaj; Maurya, Priya; Kumar, Pankaj; Katiyar, Alok (2023 5th International Conference on Advances in Computing, Communication Control and Networking (ICAC3N), 2023)
In recent years, there have been considerable developments in web development, and ReactJS has become a potent tool for creating effective and engaging web apps. This abstract offers a succinct synopsis of the study's research paper on ReactJS-based web development. [1] The purpose of the study article is to examine ReactJS's main characteristics, benefits, and potential uses in web development. It explores subjects including ReactJS' component-based architecture, virtual DOM, reconciliation method, and advantages of React Hooks. The paper also covers ReactJS's support for server-side rendering and its interoperability with the creation of mobile apps using React Native [14]. The research paper also emphasises the benefits of adopting ReactJS in online development, including better performance with the virtual DOM, reusable code, increased user interface creation, and SEO friendly web applications. As well investigates the strong ReactJS ecosystem and developer support available. The construction of a real-time chat application and a data visualisation dashboard are showcased as case studies in the article to explain the practical applications of ReactJS. Additionally, it contrasts ReactJS with two other well-known web development frameworks, Angular and Vue.js, in order to assist readers, grasp the unique qualities and applications of each framework.